Employee Service and Hotel Facilities as Determinants of Visitors' Interest in Staying - Dhedhy Purwanto; Remaoun Mohamed; Amani Metwally Ibrahim Elbatrawy (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the influence of employee service and hotel facilities on visitors’ intention to stay at Hotel Semesta Semarang. The study also seeks to examine how Islamic hospitality values contribute to shaping visitors’ perceptions and behavioral intentions in the hospitality industry. Methodology: This study employed a quantitative explanatory survey design involving 100 hotel visitors selected using purposive sampling techniques. Data were collected through questionnaires, observations, interviews, and documentation. The research instrument used a Likert scale and was tested using Pearson Product Moment validity and Cronbach’s Alpha reliability tests. Data analysis was conducted using descriptive statistics and multiple linear regression analysis with SPSS software. Main Findings: The findings revealed that employee service and hotel facilities positively and significantly influence visitors’ intention to stay at Hotel Semesta Semarang. Employee friendliness, responsiveness, professionalism, cleanliness, comfort, and security were identified as dominant factors influencing visitors’ behavioral intentions. The implementation of Islamic hospitality values also strengthened visitors’ emotional comfort and increased their intention to revisit and recommend the hotel to others. Novelty/Originality of this study: The novelty of this study lies in the simultaneous examination of employee service and hotel facilities within the context of an Islamic-themed hotel. Unlike previous studies focusing mainly on customer satisfaction, this research specifically analyzes visitors’ intention to stay while integrating Islamic hospitality values, employee ethical behavior, and religiously oriented facilities into hospitality management research.